L'utilisation de nouveaux fils synthétiques a la confection des madragues marines sur le littoral roumain de la Mer Noire - Jelescu, Nicolae; Boghici, Viorica (Cercetări Marine - Recherches Marines, 2026)
The authors present the results of the experimentation in marine set net with trap manufacturing of a large of synthetic fibers: polyamides, polyesters, polyolefins and polyvinyl alcohols. Materials durability was proved by breaking strength determination. Correlation between durability and cost leads to the conclusion that the most advantageous are polyesters fibers and polyvinyl alcohols.